"V‐Reverse" Suturing Technique for Tunnel Soft Tissue Graft and Flap Stabilization: Technique Illustration. Issue 3 (3rd December 2020) - Chacón Ramírez, Gerardo José; Tavelli, Lorenzo; Barootchi, Shayan; Wang, Hom‐Lay
Abstract : Introduction: In periodontal and peri‐implant plastic procedures, proper stabilization of the graft and the flap plays a crucial role in the outcomes. While the coronally advanced flap allows for better access with the possibility of suturing the graft to the periosteum and the de‐epithelialized papillae, there is little evidence regarding what is the best approach in stabilizing the graft and the flap when performing the tunnel techniques (TUN). The purpose of this technical note is to describe a new suturing technique "V‐reverse" for stabilization of the graft and the flap during a TUN procedure. Case Presentation: The V‐reverse suturing technique was used to enhance the stabilization of the graft and the flap during root coverage procedures, papilla augmentation, and immediate implant placement. Other advantages of this technique include reduced flap and graft micromotion; simple, easy, and fast procedure; and high patient compliance. Conclusions: The present article describes three main clinical scenarios in which V‐reverse suturing technique is used to stabilize TUN + connective tissue graft for root coverage procedures, papilla augmentation, and immediate implant placement.